THE ROLE OF PROTEIN INTAKE OPTIMIZATION IN STRENGTHENING OF CHILDREN’S HEALTH - E. F. Lukushina; O. K. Netrebenko; E. Yu. Baskakova; S. P. Gurenko (Вопросы современной педиатрии, 2013)
This study covers the problem of the optimization of protein intake by infants, the development of prolonged effects of inappropriate nutrition, comparative assessment of breast and cow milk protein, as well as the modern modifications of protein components of artificial milk formulas.